Exploring Elements of Gender Stereotypes and Stereotyping in some Zulu Wedding Songs - Khayelihle Excellent Khumalo; Bongephiwe Dlamini-Myeni (E-Journal of Humanities, Arts and Social Sciences)
The Zulu people constitute an ethnic group of related people with the same culture and traditions and predominantly inhabit the KwaZulu-Natal Province of South Africa. The Zulu’s are rooted in their culture and, therefore, are cultured people who embrace most, if not all, of their cultural beliefs. Songs are one of the tools and an integral part of the Zulu people’s folklore deployed to transmit information about cultural experiences, practices and traditions from one generation to another. This qualitative study aimed to explore gender stereotyping as portrayed in selected Zulu wedding songs. The study focuses on female gender stereotypes and stereotyping. The researchers analysed seven (n=7) purposively selected songs. Utilising critical discourse analysis, the study analysed the data collected from the lyrics of the seven selected wedding songs. The data was collected through direct observation which was done on three different wedding ceremonies that were attended by the researchers in KwaZulu-Natal in UMkhanyakude District. The songs were recorded, transcribed, and arranged in accordance with the generated themes. The study employed the Nego- Feminist Theory as the core analytical tool that framed this study. The research findings have, in essence, shown that songs among the Zulu people are reflective of gender stereotypes being upheld mainly owing to the patriarchal nature of the Zulu society. Therefore, the findings of the study further confirmed the notion that Zulu traditional wedding songs perpetuate social and gender inequalities rather than challenge the several stereotypes and stereotyping that promote gender inequality, injustice, and the typical gendered roles existing in Zulu society.